2016
DOI: 10.1016/j.reseneeco.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Club convergence and clustering of U.S. energy-related CO 2 emissions

Abstract: This study examines the convergence of energy-related carbon dioxide emissions among a panel of U.S. states between the period 1960-2009. This examination is carried out by means of a two-stage procedure. In the first stage, we conduct a novel regression-based convergence test. Unlike previous studies, this methodology endogenously identifies groups of states with emissions that are converging to a similar steady state growth path over time. In the second stage, we evaluate the rate of convergence (beta-conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 45 publications
0
44
0
1
Order By: Relevance
“…Several previous studies present evidence on CO 2 convergence, and overall this work can be divided into two main categories: (a) a relatively rich empirical literature investigating convergence of CO 2 emissions among countries worldwide has emerged (see Pettersson et al, 2014 for a recent literature review); and (b) a more limited set of studies addressing CO 2 convergence across regions (e.g., Aldy, 2007;Baldwin and Sue Wing, 2013;Burnett, 2013;Huang and Meng, 2013;Zhao, 2014) as well as across sectors (e.g., Moutinho et al, 2014;Wang and Zhang, 2014) in one single country. The latter category has a strong emphasis on China and the USA.…”
Section: Background To the Co 2 Convergence Literaturementioning
confidence: 99%
“…Several previous studies present evidence on CO 2 convergence, and overall this work can be divided into two main categories: (a) a relatively rich empirical literature investigating convergence of CO 2 emissions among countries worldwide has emerged (see Pettersson et al, 2014 for a recent literature review); and (b) a more limited set of studies addressing CO 2 convergence across regions (e.g., Aldy, 2007;Baldwin and Sue Wing, 2013;Burnett, 2013;Huang and Meng, 2013;Zhao, 2014) as well as across sectors (e.g., Moutinho et al, 2014;Wang and Zhang, 2014) in one single country. The latter category has a strong emphasis on China and the USA.…”
Section: Background To the Co 2 Convergence Literaturementioning
confidence: 99%
“…We contribute to the existing literature by comparing productivity levels and developments among OMS and NMS using farm-level data, which provide the most comprehensive indicator of productivity. According to Timmer et al (2010) a coherent 2 Club Convergence occurs when different, clubs or groups of countries with similar growth trajectories can be observed (Burnett, 2013). cross-country comparison should be based on relative levels.…”
Section: Introductionmentioning
confidence: 99%
“… Club Convergence occurs when different, clubs or groups of countries with similar growth trajectories can be observed (Burnett, ). …”
mentioning
confidence: 99%
“…Herrerias [20] utilized the distribution dynamics approach to analyze the convergence of CO 2 emissions per capita among the EU-25 countries between 1920 and 2007 and found that the convergence patterns differ strongly before and after World War II. Burnett [21] utilized the two-stage procedure to examine the convergence of the states in the U.S. and obtained the conclusion that 26 states converged to a unique steady-state equilibrium. Yang et al [22] examined the SO 2 geographical distributions in 113 main cities of China and found that the cities located in the north of the country are heavily polluted, while cities with low pollution levels mainly agglomerate in the south.…”
Section: Introductionmentioning
confidence: 99%